The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31372//20200501.1082
|View full text |Cite
|
Sign up to set email alerts
|

What Works in Mindfulness Interventions for Medically Unexplained Symptoms? A Systematic Review

Abstract: Background/Purpose: Mindfulness-based interventions (MBIs) have been used in medically unexplained symptoms (MUS). This systematic review describes the literature investigating the general effect of MBIs on MUS and identifies the effects of specific MBIs on specific MUS conditions. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis Guidelines (PRISMA) and the modified Oxford Quality Scoring System (Jadad score) were applied to the review, yielding an initial 1,556 articles. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This finding corresponds to a recent systematic review investigating the general effects of mindfulness-and acceptance-based interventions and suggesting that a qualified supervisor oversaw the facilitators to ensure faithful adherence to the mindfulness theoretical fundamentals (206). However, the mindfulness-and acceptance-based interventions emphasise a dynamic relationship between facilitators and participants that is not easy to capture and measure.…”
Section: Effects Of Mindfulness-and Acceptance-based Interventions Fo...supporting
confidence: 84%
See 1 more Smart Citation
“…This finding corresponds to a recent systematic review investigating the general effects of mindfulness-and acceptance-based interventions and suggesting that a qualified supervisor oversaw the facilitators to ensure faithful adherence to the mindfulness theoretical fundamentals (206). However, the mindfulness-and acceptance-based interventions emphasise a dynamic relationship between facilitators and participants that is not easy to capture and measure.…”
Section: Effects Of Mindfulness-and Acceptance-based Interventions Fo...supporting
confidence: 84%
“…Another systematic review and meta-analysis that included cognitive-behavioural therapy, MBCT, and ACT showed reduced FM symptoms such as pain, negative mood, and disability compared to control interventions (205). A recent systematic review that investigated the general effects of mindfulness-based interventions (MBSR, MBCT) in medically unexplained symptoms, including FM, showed beneficial effects on symptom severity, pain intensity, depression, and anxiety (206). We had also predefined fatigue, psychological distress, and work ability as outcome measures in the SR, but these measures were not assessed separately in any of the included studies.…”
Section: Effects Of Mindfulness-and Acceptance-based Interventions Fo...mentioning
confidence: 99%
“…Hence, all of these three “third wave” therapies could have a positive impact on emotion regulation processes and interrupt patients' reinforcement processes related to their symptoms ( 8 ), thus also reducing comorbid depression and anxiety ( 4 ). Efficacy of these therapies has already been shown for some specific functional somatic syndromes or symptoms [e.g., ( 9 , 10 )]. However, no meta-analysis in the field provides sufficient evidence for “third wave“ therapies taking into account recent changes in classification.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in emotion regulation is crucial in patients with somatic complaints as a lack of emotional awareness and an overuse of maladaptive emotion regulation strategies are considered basic psychological liabilities of Somatic Symptom Disorder (Waller and Scheidt, 2004;Garnefski et al, 2017;Okur Güney et al, 2019). Previous research has shown that mindfulness meditation can have a positive impact on some aspects of somatization, such as symptom severity and pain intensity, and on comorbid anxiety and depression (Hoge et al, 2013;Lakhan and Schofield, 2013;Aucoin et al, 2014;Hilton et al, 2017;Hazlett-Stevens, 2018;Billones et al, 2020). However, the body of evidence prevents strong conclusions, as available studies are mostly based on mindfulness interventions, in which social determinants, such as the relationship with the instructor and the group, have been found to be stronger predictors than specific mindfulness practice-related factors on psychological outcomes (Canby et al, 2021).…”
Section: Introductionmentioning
confidence: 99%